Perancangan Interior Relish Cafe & Lounge di Surabaya - Felicia Dewi Chrisanti S.; mariana wibowo; dody wondo (Intra, 2013)
Cafe & Lounge as a place to gather together, enjoy eating and drinking also doing a variety of activities become an essential place in the life of today's society. Relish Cafe & Lounge is designed to be a public place that can accommodate the community to meet the need for socializing, a comfortable place to enjoy food and beverage offerings, and for hobby activities such as reading books, events photography, as well as to do the job like a business agreement or deal and so on. Attractive design, capable of attracting visitors to come in, therefore therefore, the modern gothic style design chosen because it has elements of a timeless classic but still keep up with the times. The concept offered is Rose Garden, which has meaning beauty, timeless, balance, secret, mysterious and romantic feel also many variations or options that are offered to visitors. Concept and design style is applied both in the use of chandeliers for lighting, wallpaper with roses pattern, checkerboard pattern and rose motifs on the floor, window and wall framelis pointed arch shaped, carved gothic oak leaf foliage, red, purple, black , and a cream colors is applied to the furniture, also other decorative elements in the interior and the interior design of the Relish Cafe & Lounge in order to attract customers to come in and enjoy the facilities inside.